Wild food plant knowledge in multicultural peri-urban area of North-Western Punjab, Pakistan - Amna Malik; Muhammad Adnan; Fahdah Falah ben hasher; Arshad Mehmood Abbasi; Mansour K. Gatasheh; Zahid Ullah; Ali Abdullah Aldosari; Hazrat Ali; Muhammad Abdul Aziz (BMC, 2024)
Abstract The use of wild food ingredients has been inextricably linked to each human culture; therefore, any cultural shift or transformation also mutates the knowledge. Particularly cross-cultural interactions have been playing a significant role in reshaping the knowledge within a given community. The study aimed to cross-culturally research the use of wild food plants among four different ethnolinguistic groups, i.e. Muhajir, Pathans, Punjabi, and Saraiki residing in the peri-urban area of Mianwali district, Punjab Pakistan. Data were taken through semi-structured interviews, and the results of cross-cultural comparison were visualized through Venn diagrams and statistically tested through Jaccard index. A total of 59 plants were recorded, which were used mostly as cooked vegetables (29 species) and snacks (21 species). About one-fourth of the quoted plants were commonly used by all the studied groups. High similarity on the use of the quoted plants was found among Muhajir, Punjabi, and Saraiki. Punjabi reported higher numbers of plants, and Pathans quoted comparatively lesser number. Pathans reported a comparatively high number of idiosyncratic foods uses followed by Muhajir. Punjabi, Muhajir, and Saraiki have a very close affinity and have comparatively rich knowledge after comparing those food uses which were reported by more 50% of participants. Punjabi frequently reported some plant uses which were rarely reported by the other four groups. Additionally a large number of plants were also quoted along with their medicinal uses which were prepared in the same way for both food and medicine. Despite the fact that most of the food ingredients were prepared in a simialr way but still the distinct names of several plants were retained across the studied groups. In the current context, the ethnobotanies of the studied communities are a blend as they might have learned the knowledge on the use of these plants from one another. It is concluded that since the knowledge is still in the memory of the people and has no serious threat to its extinction at hand, however it is necessary to frame policy programs in order to use this knowledge for the sustainability of future food and medical system otherwise it may be lost.